2009
DOI: 10.1038/labinvest.2009.108
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of a functional autoantibody in narcolepsy by a cholinesterase inhibitor

Abstract: We have recently reported the presence of an immunoglobulin G (IgG) autoantibody (Ab) in patients with narcolepsy with cataplexy that abolishes spontaneous colonic migrating motor complexes (CMMCs) and increases smooth muscle tension and atropine-sensitive phasic contractions in a physiological assay of an isolated colon. In this study, we used the cholinesterase inhibitor, neostigmine, to explore the mechanism of the narcoleptic IgG-mediated disruption of enteric motor function in four patients with narcoleps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…27 Although narcolepsy is associated with HLA and TCRA polymorphisms, autoantibodies specific to HCRT cells have been difficult to detect reliably using immunocytochemistry, western blots and other assays. 16,28,29 Jackson et al 30 suggested the presence of autoantibodies interfering with colonic migrating contractions and bladder contractile responses using functional assays in animals, but this work awaits replication. The fact anti-TRIB2 antibodies are primarily found in recent onset cases, suggests the need for searching new autoimmune markers in this population.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although narcolepsy is associated with HLA and TCRA polymorphisms, autoantibodies specific to HCRT cells have been difficult to detect reliably using immunocytochemistry, western blots and other assays. 16,28,29 Jackson et al 30 suggested the presence of autoantibodies interfering with colonic migrating contractions and bladder contractile responses using functional assays in animals, but this work awaits replication. The fact anti-TRIB2 antibodies are primarily found in recent onset cases, suggests the need for searching new autoimmune markers in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-M3R are not exclusive to Sjögren's syndrome, but also occur in Sceleroderma [67], dermatomyositis [105] and Narcolepsy [106][107][108]. The putative anti-M3R in the IgG fraction in these conditions appear functionally indistinguishable from those seen in Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 94%